Kebijakan Publik dalam Krisis Akuntabilitas: Studi Kasus PT Juya Aceh Mining di Kabupaten Aceh Barat Daya - Syarkawi Syarkawi; Anggi Anggraeni Kusumoningtyas; Jhonny Syaputra S (Yayasan Literasi Sains Indonesia, 2026)
This study analyzes the accountability crisis in the implementation of public policy in the mining sector through a case study of PT Juya Aceh Mining (PT JAM) in Southwest Aceh Regency. This study uses a descriptive qualitative approach with content analysis of regional regulations, media reports, and academic literature. The analytical framework refers to Van Meter and Van Horn's policy implementation theory, UNDP's good governance principles, and the perspective of public policy ethics. The results of the study show weak transparency, oversight, and public participation in mine management, as well as a lack of moral integrity among policy makers. The CSR program is symbolic in nature, does not involve the community in a participatory manner, and lacks clear accountability mechanisms. These conditions have triggered social tensions, land conflicts, environmental damage, and a decline in public trust in the government and the company. PT JAM's activities are considered to reflect policy failure and public ethics violations, as the local government has not effectively carried out its role of oversight and protection of the community. This study emphasizes that successful public policy requires not only good regulations, but also ethical commitment, bureaucratic capacity, and public control mechanisms. Strengthening governance based on transparency, accountability, and participation is a prerequisite for preventing conflict and ensuring sustainable natural resource management.